An Hypothesis for CXCL1/CXCR2 Signaling Regulating Neutrophil-Derived Opioid Peptides Involved in Acupuncture for Inflammatory Pain. (21st April 2021) - Ding, Sha-sha; Xu, Yuan; Zhang, Ying-ying; Chen, Jing-zi; Hong, Shou-hai
Abstract : Increasing evidences demonstrate that acupuncture is effective in treating inflammatory pain. Recent studies have found that peripheral endogenous opioid peptides in the area of inflammation are involved in acupuncture-treating inflammatory pain. However, the source of endogenous opioid peptides in local area of inflammation and the mechanism of acupuncture regulating these opioid peptides remain unclear. Studies have demonstrated that neutrophils infiltrated in the inflamed tissue contain and release opioid peptides. Chemokine (C-X-C motif) ligand 1 (CXCL1) is one of the key neutrophil chemokines and can promote the blood neutrophil recruitment to the area of inflammation. In our previous experiments, we found that acupuncture could alleviate inflammatory pain and significantly increase the concentration of chemokine CXCL1 in the blood of rats with inflammatory pain. So we suppose that increased concentration of CXCL1 by acupuncture could activate the blood opioid-containing neutrophils via its main receptor chemokine receptor type 2 (CXCR2) and promote them recruit to the inflamed tissue to release opioid peptides, participating in the analgesic effect of acupuncture.